ANALISIS PERILAKU DISIPLIN TERHADAP KARAKTERISTIK KEGIATAN ORGANISASI UKM SEKOLAH TINGGI ILMU EKONOMI INDONESIA JAKARTA - Rutinaias Haholongan; Nurul Rahmadlani; Nunung Nurjanah; Wanda Azzahra Nasution; Juniarli Mangule (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Disciplinary behavior is one of the factors that determine success in carrying out the activities of an organization. This study aims to analyze the relationship between disciplinary behavior and characteristics of organizational activities in seven student activity units at STIE Indonesia Jakarta. Using descriptive qualitative method, data were collected through interviews and observations of core administrators and active members from Senat Mahasiswa, Hima Manajemen, Remaja Majelis Nurul I'tishom, Sakuntala, Bulutangkis, Seni Budaya, and Karate. The results showed that participation and attendance were influenced by the level of commitment and interest in routine activities, such as training. Internal factors, such as the role of the chairman and social support among members, as well as external factors, such as a busy lecture schedule, affect the discipline of members. Efforts to improve discipline are made through member self-awareness, consistent communication, and fair application of discipline rules. A firm and wise leader and a structured schedule of activities also play an important role in improving discipline. This research reveals that high discipline will support the achievement of organizational goals, strengthen relationships between members, and improve the quality of student activity unit work results.